Money and banking in Malaysia - The Economics Department; Bank Negara Malaysia (Kuala Lumpur : Bank Negara Malaysia, 1989)
The purpose of this book is to provide a simple, comprehensive and authoritative account of the evolution, structure and development of money and banking in Malaysia over the past 20 years and the role of the Central Bank in this process of transformation and in monetary management. It is also to provide a ready reference for those interested in knowing more about Malaysia's financial system and to provide a basis for an assessment of the direction in which the system may be further developed to better serve the needs of the domestic economy in the years ahead.
Includes bibliographical references and index.
rpm 07/05/2018
Loans
Keywords: Banks and banking; Money; Financial institutions; Malaysia